A Planning Model for the Divisionalized Enterprise. - Farag, Shawki M. (The Accounting Review, 1968)
The article presents a micro input-output model, based on some basic concept of input output theory, which can be used for planning the activities of divisionalized enterprises. The continuing growth of the business enterprise in size and complexity places steady pressure on business accounting to find more effective ways of planning and controlling business operations. The author states that there are three pure types of models, iconic, analog and symbolic. The micro input-output model proposed here is a mathematical model of the deterministic type. The accountant who wants to use mathematical models in solving practical business problems has two main tasks. The first is to formulate a description of a problem in terms of mathematical equations. The second is to solve and interpret the equations. The first of these, frequently referred to as the building of the mathematical model, is often the more difficult. The underlying assumptions involved in the model are also stated in the article in order to clarify the nature and structure of the micro input-output model.